Creators and Presses: The Person–Situation Interaction in Negative Creativity. (7th May 2018) - Kapoor, Hansika; Khan, Azizuddin
Abstract: Given the recent emphasis on exploring valence in creative behavior, this study examines negative creativity via a person–situation interactionist perspective. By manipulating goal valence (uses or misuses) and object valence (positive or negative), four conditions of an adapted Divergent Thinking task were used to predict positive and negative creativity. Participants ( N = 178, 103 females, M age = 23.82, SD = 4.03, range: 18–38) responded to a single condition along with the Big Five and Dark Triad personality scales in a between‐groups design. Hierarchical multiple regressions revealed that goal and object valence significantly explained variance in valences of creative responses, beyond individual differences of personality. Furthermore, the congruence between goal and object valence predicted valenced creativity; that is, the positive objects and goals condition yielded more positive‐original ideas, and the negative objects and goals condition yielded more negative‐original ones. Object valence alone (material presses) did not contribute significantly to explaining valenced creativity. Negative‐original responses were inversely related to conscientiousness, and directly to intellect/imagination and secondary psychopathy. Thus, negative creativity was attributed relatively more to person as compared to situation variables. Results are discussed from a valence‐based and interactionist perspective.